A simplified radiographic score effectively predicts radiographic progression of early arthritis in a large nationwide French cohort. (19th October 2019) - Carvajal Alegria, Guillermo; Milin, Morgane; Gandjbakhch, Frédérique; Saraux, Alain; Bailly, Florian; Jousse-Joulin, Sandrine; Schaeverbeke, Thierry; Lukas, Cédric; Foltz, Violaine; Fautrel, Bruno; Devauchelle-Pensec, Valérie
Abstract: Objective: Evaluating radiographic progression is a key component of the follow-up of patients with RA. Existing scores are ill-suited to everyday clinical practice. The objective here was to validate a new simplified radiographic score (SRS) for evaluating radiographic progression in patients with early arthritis. Methods: Patients with arthritis of <6 months' duration were included in the large, prospective, nationwide, French ESPOIR cohort. Radiographs of the hands and feet were obtained at inclusion then 1 and 5 years later. The modified Sharp scores and SRS were determined by blinded readers. Interobserver reliability and intraobserver repeatability of each score, as well as agreement between the two scores, were assessed by computing the intraclass correlation coefficients. The rates of progression over the first year and the next 4 years were determined. Results: The 506 patients with complete data for the first 5 years were included. At inclusion, the intraclass correlation coefficient between the two scores was good for erosions (0.715, P < 0.001), joint space narrowing (0.892, P < 0.001) and the total score (0.896, P < 0.001). Agreement between the two scores was also good for radiographic progression after 1 year (0.781, P < 0.001). The SRS had good positive and negative predictive values for slow and for rapid progression. SRS determination was less time consuming. Conclusion: The SRS is effective for monitoring radiographic progression in early arthritis and is easier to use and less time-consuming than the Sharp score. The usefulness of the SRS in clinical practice deserves further evaluation.